Chylous peritonitis in peritoneal dialysis - Hanen Abid; Salma Toumi; Hanen Chaker; Beya Fandri; Ikram Agrebi; Najla Dammak; Fatma Mseddi; Khawla Kammoun; Soumaya Yaich; Mohamed Ben Hmida (RDPLF, 2021)
Chylous peritonitis (CP) is a rare complication in patients on peritoneal dialysis. There are many reasons for this. It can occur as a result of a traumatic insertion of the peritoneal dialysis catheter or secondary to infectious or drug causes. The evolution is favorable at the elimination of the causative agent. We report 3 cases of PC occurring in 3 patients on peritoneal dialysis. In 2 patients, CP was secondary to calcium channel blockers and in 1 case associated with lymph node tuberculosis. The cessation of the causative agent allowed a clarification of the effluent dialysate. CP is a mild form of non-infectious peritonitis that is often confused with infectious peritonitis. In this article we discuss the etiologies of CPs, the pathophysiology and the conduct to be held in front of a CP.